Attenuated cardiac autonomic modulation and cognitive performance in overtrained athletes - Hynynen, E.; Uusitalo-Koskinen, A.; Konttinen, N.; Rusko, H. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Twelve severely overtrained [OA, 6 men and 6 women, mean age (±SD) 25±7 yrs] and twelve control [CA, 6 men and 6 women, 24±5 yrs] athletes were examined. The athletes were reached via information sent to Finnish sport magazines, Finnish sport unions, about 500 Finnish physicians taking care of athletes, and all the centers of sport medicine in Finland. Overtraining state was diagnosed using the following criteria: an athlete 1) had suffered from unexplained decrement in physical performance and fatigue even after recovery time of at least 3 weeks, 2) had been examined to be otherwise healthy, and 3) had suitable training history for overtraining state. Nocturnal RR-intervals (RRI) and urine samples were collected at home, as well as RRI during an active orthostatic test (5-min supine rest and 3-min standing; physical test) in the morning. RRI were also collected during the Stroop Colour Word Test at constant velocity (SCWT; cognitive test), and during a succeeding 14-min relaxation exercise guided from a tape recorder in a quiet laboratory room. RRI were collected with RR-recorder (Polar Electro, Kempele, Finland). HRV parameters were calculated according to Task Force (1996) and urine stress hormones (adrenaline, noradrenaline, and cortisol) were analysed by liquid chromatography. Ln-transformation was used in not-normally distributed variables, and Student`s t-test was used for statistical testing. Results SD of RRI (RRSD) and low frequency power of RRI (LFP) during supine rest, and during standing were lower in overtrained athletes (Table 1). In SCWT OA made more mistakes. No differences were found in average RRI (RRave), and in high frequency power of RRI (HFP) during supine rest, standing, and SCWT. However, in CA total power of RRI (LFP + HFP) increased more from the SCWT to relaxation than in OA (from 1,2±0,8 to 5,0±3,3 vs. from 1,8±2,5 to 3,6±3,8 ·103 ms2, p = 0.039, respectively). No differences were found in nocturnal RRave, HRV, and the urine stress hormone concentrations between the groups. Discussion/Conclusion Overtrained athletes had lower HRV, and lower autonomic responses to relaxation than controls, which refers to attenuated cardiac autonomic modulation in OA. Cognitive function of OA was diminished, as indicated by more mistakes during SCWT than controls. Previous controlled overtraining studies concerning HRV are scarce and the results are controversial (Uusitalo et al 2000). Concentrations of nocturnal stress hormones have been reported to change during the development of overtraining state (e.g. Lehmann et al 1998), but the results have been controversial, and we did not find any differences between the groups. In conclusion, our findings suggest that cardiac autonomic modulation, as well as cognitive function in the overtrained athletes were attenuated.